Pengaruh Kualitas Pemerintahan Terhadap Penanaman Modal Asing (Studi Empiris Pada Negara ASEAN Tahun 2009-2013) - Drajat, Estu Unggul; Manzilati, Asfi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
This study is aimed to examine the influence of government quality towards Foreign Direct Investment (FDI). This study uses a quantitative method using secondary data. The sample was ASEAN countries in 2009-2013. The result of this study shows that voice and accountability and rule of law has significant positive influence towards FDI. While political stability and absence of violence/terrorism, government effectiveness, regulatory quality, and control of corruption has not influence towards FDI.Keywords: quality of governance, World Governance Indicators (WGI), Foreign Direct Investment (FDI)